Effects of Microfinance Intervention on Multiple and Non-multiple Financing Clients: A Case of Gandaki Province of Nepal (Journal of Nepalese Business Studies, 2020)
The objective of this study is to examine the effects of microfinance intervention on multiple and non-multiple borrowings clients in the Gandaki province of Nepal. Further, the study aims to explore the reasons for multiple borrowings and the impact of microfinance intervention on micro-enterprise creation, total investment, profit per month, income, and saving. The research is based on primary sources of data and confined to Muktinath Biikas Bank Limited (MBBL). Microfinance clients involving MBBL for the last five or more years are the respondents, and 311 MF clients were randomly selected from 10 branches of MBBL. Both descriptive and inferential statistics have been applied to find out the effects of microfinance intervention. The key reasons behind multiple financing are forced by friends, the presence of other MFIs, insufficient loan, meeting domestic requirements, repaying other MFIs loan, lending to others at high interest, and repaying a high-interest loan. There are significant differences between multiple and non-multiple financing clients in terms of micro-enterprise creation, total investment, profit per month, and saving. The result shows that non-multiple financing clients are more likely to earn more profit, create new business, and have the potential for large-scale investment. The mean score shows that non-multiple financing clients are saving more than multiple financing clients, indicating more commitment to saving for future funds requirement to expand the business. At last, the study concluded that the performance of non-multiple financing clients is significantly better than multiple financing clients. Since multiple financing creates problems if it is not controlled properly, so microfinance institutions (MFIs) and regulatory authorities should discourage multiple borrowing practices through proper regulation, adequate supply of loans, and its productive orientation.